2012
DOI: 10.1063/1.3681367
|View full text |Cite
|
Sign up to set email alerts
|

Optical detection of melting point depression for silver nanoparticles via in situ real time spectroscopic ellipsometry

Abstract: Silver nanoparticle films were deposited by sputtering at room temperature and were annealed while monitoring by real time spectroscopic ellipsometry (SE). The nanoparticle dielectric functions (0.75 eV–6.5 eV) obtained by SE were modeled using Lorentz and generalized oscillators for the nanoparticle plasmon polariton (NPP) and interband transitions, respectively. The nanoparticle melting point could be identified from variations in the oscillator parameters during annealing, and this identification was furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…For example, Yeschenko et al 9 showed that the melting point of silver nanoparticles embedded in a silica matrix varied between 350 o C (30 nm diameter) and 160 o C (8 nm diameter). A reduction in the melting temperature was also seen recently by Little et al for silver films formed into nanometer sized islands on Si substrates 10 ; both approaches employed optical (plasmon based) methods to determine the onset of melting.…”
Section: Introductionsupporting
confidence: 57%
“…For example, Yeschenko et al 9 showed that the melting point of silver nanoparticles embedded in a silica matrix varied between 350 o C (30 nm diameter) and 160 o C (8 nm diameter). A reduction in the melting temperature was also seen recently by Little et al for silver films formed into nanometer sized islands on Si substrates 10 ; both approaches employed optical (plasmon based) methods to determine the onset of melting.…”
Section: Introductionsupporting
confidence: 57%
“…The shape deformation and melting point decrease of nanoparticles was observed and described earlier for different types of nanoparticles [13][14][15][16]. The lower melting point compared to the bulk material is due to the large surface-to-volume ratio, which results in an increase in the surface free energy of the particles [17].…”
Section: Introductionmentioning
confidence: 87%
“…Consistency is suggested because highly disordered or even liquid films are expected to exhibit a single TL and can form atomically smooth surfaces upon coalescence [51]. A liquid film is a possibility due to the reduction in the melting point from the bulk that can occur in clusters and very thin films, as observed in RTSE studies of Ag thin film deposition [52]. It is of interest to note that the compositions with the most rapid smoothening effect during coalescence are those that exhibit the highest performance when incorporated into devices.…”
Section: Rtse Results and Discussionmentioning
confidence: 99%